Structural Ambidexterity: Exploring Alternative Pro-Ambidexterity Conducive Structural Designs for Recourse-Constrained Organizations - Marri, Muhammad Yousuf Khan; Soo , Hooi Sin; Ali, Hassan (Archives of Business Research, 2020)
Organizational ambidexterity is of paramount importance for the long term success of business organizations operating in an uncertain and dynamic environment. Although the role of a structure by means of structural differentiation (structural ambidexterity) advocated and supported for attaining organizational ambidexterity, however, it has also received criticism for being counterproductive for recourse-constrained organizations. Despite the fact, less focus has been devoted to finding alternative organizational structural design approaches for predicting organizational ambidexterity in resource-deficient organizations. To heed such persisting knowledge gap, this study highlighted four possible alternative organizational structural designs that may be useful for resolving the exploration and exploitation tension and attaining organizational ambidexterity in resource-constrained originations. Such an effort will serve as a reference for future conceptual and empirical research in organizational design and ambidexterity literature.